Application of response surface methodology coupled with genetic algorithm in the optimization of cutting conditions for surface roughness in end-milling of Inconel 718 using coated WC-co inserts - Ishtiyaq, M. H.; Amin, A. K. M. Nurul; Karim, A.N. Mustafizul; Ginta, Turnad Lenggo; Patwari, Muhammed Anayet Ullah (2007)
This paper presents an efficient method of optimisation of surface roughness in end milling of Inconel 718 using TiAlN coated inserts under dry conditions by coupling response surface methodology (RSM) with genetic algorithm (GA). RSM has been utilized to develop an efficient mathematical model for surface roughness in terms of cutting parameters. For this purpose, a number of machining experiments based on statistical central composite design of experiments method are carried out. Then the developed RS model is further interfaced with the GA to optimize the cutting conditions for achieving minimum surface roughness. GA improved the surface roughness by about 12%.